Evaluation of signs of immune or metabolic disturbances among diabetic patients with positive islet cell antibodies - Ibrahim Dezayee, Zhian M.; Waheda, Nabeel E.; Said Al- Salihi, Sabria M. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: Autoantibodies to islet cell antigens are known predictors of type 1 diabetes and detected in latent autoimmune diabetes in adults.Objectives: This study aimed to identify the metabolic and immunological disturbances in diabetic patients with positive and negative islet cell antibodies (ICAs)Materials and methods: A total number of 235 known cases of diabetes mellitus type 1 (160) and type 2 diabetes (75) were admitted in the study. Serum ICA and immunoglobulins (IgA, IgM, IgG) as well lipid profile were measured.Results: Positive ICAs was found in 40 out of 120 T1D (33.3%) and 28 out of 75 T2D (37.3%). All the patients were poorly controlled diabetes with the evidence of significant high HbA1c%. There were no significant differences in the lipid profile or immunoglobulin levels between positive and negative ICAs in T1D and T2D.Conclusions: Autoimmunity in term of positive ICA does not play a role in metabolic or immunologic disturbances that associated with T1D and T2D.